Interventional therapy in patients with severe emphysema: evaluation of contraindications and their incidence - Polke, Markus; Rötting, Matthias; Sarmand, Nilab; Krisam, Johannes; Eberhardt, Ralf; Herth, Felix; Gompelmann, Daniela (Therapeutic advances in respiratory disease, 2019)
Background: Endoscopic and surgical interventions may be beneficial for selected patients with emphysema. Rates of treatment failure decrease when the predictor...
Gesehen am 11.12.2019